2015
DOI: 10.22436/jnsa.008.06.07
|View full text |Cite
|
Sign up to set email alerts
|

On strong and Δ -convergence of modified S-iteration for uniformly continuous total asymptotically nonexpansive mappings in CAT(κ) spaces

Abstract: In this paper, we obtain strong and ∆-convergence theorems of modified S-iteration for total asymptotically nonexpansive mappings in CAT(κ) spaces with κ > 0. Our results extend and improve the corresponding recent results announced by Panyanak [B. Panyanak, J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Our results not only give an affirmative answer to the above open question but also generalize the results of Wangkeeree and Preechasilp [25], Liu and Chang [18], Kumam et al [17], Saipara et al [22], and many others. Some related results in R-trees are also given.…”
Section: Theorem 12 ([18]supporting
confidence: 88%
“…Our results not only give an affirmative answer to the above open question but also generalize the results of Wangkeeree and Preechasilp [25], Liu and Chang [18], Kumam et al [17], Saipara et al [22], and many others. Some related results in R-trees are also given.…”
Section: Theorem 12 ([18]supporting
confidence: 88%
“…Also, there were many authors who have studied about this iterative process for estimate a fixed point in various spaces and them results showed that the rate of convergence for this iterative process is much quicker than another iterative process (see e.g., [38,39,40,41,42]). …”
Section: Modified Random Errors S-iterative Processmentioning
confidence: 99%
“…Denote by 25) then {x n } converges weakly to a point x * ∈ Ω which is a minimizer of f in C as well as it is also a fixed point of T in C.…”
Section: Lemma 27 ([28]mentioning
confidence: 99%